Advanced technologies in periodontal tissue regeneration based on stem cells: Current status and future perspectives - Wen-Yi Zeng; Yang Ning; Xin Huang (Elsevier, 2021)
Periodontitis is a progressive inflammation disease, the clinical management of which remains a challenge. The traditional management may control periodontal inflammation, but failed to regenerate functional periodontium. This review summarizes the most advancing regenerative techniques regarding stem cell culture and scaffold fabrication, such as cell sheeting, spheroid culture, electrospinning and 3D printing. The applications of different techniques manifest tremendous potential of regenerating the complete and functional periodontium. Albeit promising, new technologies have met with their own drawbacks such as insufficient vascularization and precision, which necessitate deeper modification. Thus, this review also points out the potential perspectives and methods aiming at their disadvantages, illuminating the directions of future researches to successful clinical scenarios.